DC32, a Dihydroartemisinin Derivative, Ameliorates Collagen-Induced Arthritis Through an Nrf2-p62-Keap1 Feedback Loop - Fan, Menglin; Li, Yanan; Yao, Chunhua; Liu, Xiufeng; Liu, Jihua; Yu, Boyang (Frontiers in Immunology, 2018)
Artemisinins have been reported to have diverse functions, such as antimalaria, anticancer, anti-inflammation, and immunoregulation activities. DC32, a dihydroartemisinin derivative possessing potent immunosuppressive properties, was found in our previous study. In this study, the antirheumatic effect and underlying mechanisms of DC32 were investigated. The results showed that DC32 could markedly alleviate footpad inflammation, reduce cartilage degradation, activate the Nrf2/HO-1 signaling pathway, and increase the transcription of p62 in DBA/1 mice with collagen-induced arthritis (CIA). Further mechanistic exploration with NIH-3T3 cells indicated that DC32 could increase the transcription, expression and nuclear translocation of Nrf2. In addition, DC32 promoted degradation of Keap1 protein and upregulated HO-1 and p62 expression. Furthermore, the effect of DC32 on Keap1 degradation could be prevented by p62 knockdown using siRNA. Administration of DC32 could inhibit the phosphorylation of Akt/mTOR and ERK, and pretreatment of NIH-3T3 cells with the autophagy inhibitor 3-methyladenine (3-MA) attenuated the degradation of Keap1 induced by DC32. These results suggest that DC32 inhibits the degradation of Nrf2 by promoting p62-mediated selective autophagy and that p62 upregulation contributed to a positive feedback loop for persistent activation of Nrf2. In summary, our present study demonstrated that DC32 significantly suppressed rheumatoid arthritis (RA) via the Nrf2-p62-Keap1 feedback loop by increasing the mRNA and protein levels of Nrf2 and inducing p62 expression. These findings provide new mechanisms for artemisinins in RA treatment and a potential strategy for discovering antirheumatic drugs.